Comparison of Actual Deformations of Historic Wooden Structures with Values Obtained from Static Calculations - Zimiński, Kamil; Pawłowicz, Joanna A. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In historic wooden structures, deformations can be influenced by factors that are negligible within the first 50 years of the building`s existence. In attics where the roof covering is made of metal sheets, the air and structural elements heat up during the day and cool down rapidly at night. This phenomenon, over a long period, can cause micro-cracks and surface material degradation. For the study, historic buildings meeting the criteria for service class II according to PN-EN 1995-1-1 were selected. Measurements of deflections, humidity, and modulus of elasticity of the wood were conducted. The actual deflections of the examined structures were found to be 28% to 37% higher than those obtained from numerical calculations, indicating ongoing rheological processes in the wooden structures.
Keywords: wooden structures; non-destructive testing; laser scanning; old timber; old timber structures; old wood; againg effect; mechanical properties assessment; timber creep